Einsatzgruppen: The Death Brigades Part II: Funeral Pyres (1942-1945) UNCENSORED - Best Documentary et World at War (NC, 2026)
Vidéo YouTube proposée par Best Documentary et World at War. Nazi mobile killing squads, led by highly-educated officers and aided by local collaborators, systematically murdered over.
Droits : Vidéo publique YouTube. Droits conservés par le diffuseur.
Keywords: vidéo; youtube; culture; arts; documentaire; Culture